KAPAL KUNA TENGGELAM SEBAGAI ASET PENELITIAN ARKEOLOGI BAWAH AIR DAN PEMANFAATANNYA - Hari Lelono (Balai Arkeologi Yogyakarta, 2008)
In response to the fact that there is an overlapping issue over the handling of the sunken ships (shipwreck), some people believe that those are treasures which has been lifted up carelessly and then sold for the sake of economy benefit. On the other side, referring to UU No 5 Tahun 1992 defining about the Heritage Objects (Benda Cagar Budaya), those objects mentioned are included in the protected ones. How those objects could be explored depend on the efforts made by the related institutions and the archaeologists by doing some scientific research, conducting the conservations over those objects and eventually by implementing their usage aspect.